Evaluation of autonomic nervous system functions in post-stroke patients - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2002)
Objective: In this study, we aimed to investigate whether there is a sympathetic and parasympathetic system dysfunction in hemiplegic or hemiparetic patients after a cerebrovascular accident. Design: Sympathetic skin response and R-R interval variation were evaluated in a total of 65 subjects: 37 hemiparetic or hemiplegic patients due to a cerebrovascular accident, seven acute (<30 days) and 30 chronic, with a mean age of 59.16 yr (32-76 yr), and 28 healthy subjects with a mean age of 57.07 yr (45-75 yr). Disease duration was 6.89 mo (1-32 mo) in the patient group. Bilateral sympathetic skin responses were recorded with stimulation of median nerves in both affected and unaffected sides. R-R interval variation was evaluated at rest (R%) and during deep breathing (DB%) at six times per minute. Results: Although there was no significant difference between sympathetic skin response latencies of the patient and the control groups, the amplitude values of sympathetic skin response in patients were significantly lower than those in controls (P < 0.05). Both R% and DB% in patients significantly increased as compared with controls (P < 0.001 and P < 0.05, respectively). Conclusion: In conclusion, our results suggest that both sympathetic and parasympathetic functions in post-stroke survivors were partially inhibited, and this finding may be useful in the prediction of possible complications during rehabilitation.
Keywords: stroke; autonomic nervous system dysfunction; sympathetic; skin response; R-R interval variation; cerebrovascular accident; hemiparesis; hemiplegia; SYMPATHETIC SKIN-RESPONSE; RR INTERVAL VARIATION; DYSFUNCTION; STROKE